The Interplay between Mitochondrial Morphology and Myomitokines in Aging Sarcopenia - Romanello, Vanina (Int J Mol Sci, 2020)
Sarcopenia is a chronic disease characterized by the progressive loss of skeletal muscle mass, force, and function during aging. It is an emerging public problem associated with poor quality of life, disability, frailty, and high mortality. A decline in mitochondria quality control pathways constitutes a major mechanism driving aging sarcopenia, causing abnormal organelle accumulation over a lifetime. The resulting mitochondrial dysfunction in sarcopenic muscles feedbacks systemically by releasing the myomitokines fibroblast growth factor 21 (FGF21) and growth and differentiation factor 15 (GDF15), influencing the whole-body homeostasis and dictating healthy or unhealthy aging. This review describes the principal pathways controlling mitochondrial quality, many of which are potential therapeutic targets against muscle aging, and the connection between mitochondrial dysfunction and the myomitokines FGF21 and GDF15 in the pathogenesis of aging sarcopenia.